Effects of tocotrienol on aging skin: A systematic review - Ghazali, Nur Izyani; Mohd Rais, Rahimah Zahidah; Makpol, Suzana; Chin, Kok Yong; Yap, Wei Ney; Goon, Jo Aan (Frontiers in Pharmacology, 2022)
The skin is the largest organ of the body that protects us from mechanical, thermal and physical injury. However, the function and appearance of the skin visibly degenerates with growing age. This is due to the frequent exposure of the skin to harmful effects of the environment including ultraviolet irradiation and hazardous substances besides progression of oxidative stress in ageing. These factors result in phenotypic changes in the skin including wrinkling, pigmentation, reduced elasticity and hydration during ageing. Many natural antioxidant compounds have been studied extensively to reverse the signs of ageing skin. Tocotrienol is a subfamily of vitamin E with potent antioxidant activity. Therefore, supplementation with vitamin E in the form of tocotrienol may provide an efficient way of protecting the skin against ageing. In this review, the effects of tocotrienol on skin health, including pigmentation, moisture and wrinkle during ageing and UV exposure, are systematically evaluated based on a literature search of PubMed and Scopus databases. Present data showed that tocotrienols protect the skin from inflammation, UV radiation and melanin accumulation. As the therapeutic value of tocotrienols grow, the potential of these vitamin E analogues to the skin requires further investigation.